Enrichment and in-situ ceramic immobilization of uranium by mesoporous ZrO2/SBA-15. Issue 23 (1st December 2021) - Ding, Yi; Fan, Weijie; Chen, Zhenyu; Li, Zhen; Liu, Yuan; Dan, Hui; Duan, Tao
Abstract: To simplify the treatment of radioactive wastewater and reduce the secondary pollution, in this work, mesoporous ZrO2 /SBA-15 was synthesized and employed for the first time as both the adsorbents and crystalline matrices for efficient enrichment and in-situ immobilization of U in radioactive wastewater. In general, U was efficiently enriched by using the mesoporous ZrO2 /SBA-15 and then immobilized into ZrSiO4 ceramics by the followed sintering process. The U-adsorbed ZrO2 /SBA-15 was changed to stable ZrSiO4 –U ceramics by sintering at 1250–1450 °C for 6 h. The results also provided the evidence that both U(Ⅳ) and (Ⅵ) were incorporated into the crystal structure of ZrSiO4 by replacing Zr(Ⅳ). Furthermore, all the obtained ZrSiO4 –U ceramics exhibited good aqueous durability. Given the high adsorption capacity and good aqueous durability, it is expected that the ZrO2 /SBA-15 is attractive for actual applications in treatment of U containing radioactive wastewater.